Intrathoracic mass in a 5-month-old infant: fetus in fetu-a case report - Abdel-Kémal Bori Bata; Joseph Akodjènou; Gilles Modeste Alain Bognon; Simon Azandegbe Azonbakin; Romulus Takin; Jules Marouf Alao; Antoine Seraphin Gbenou; Armand Michel Fiogbe; Delphin Kuassi Mehinto (SpringerOpen, 2022)
Abstract Background The fetu in fetu (FIF) is an extremely rare congenital condition characterized by a 2nd fetus that grows into the body of the healthy twin. Its thoracic location is more exceptional. Case presentation We report a case of intrathoracic mass in a 5-month-old female infant, diagnosed after an assessment for respiratory distress. She underwent an emergency left thoracotomy which allowed for the removal of a large thoraco-mediastinal mass inside a membranous sac containing a clear liquid mixed with vernix caseosa. The mass was completely covered with normal skin, three lobes similar to rudimentary outline of the head and limb. It was attached to a single large vascular pedicle. The pathological examination concluded that there was a high possibility of FIF. The postoperative follow-up was uncomplicated, and the child is still in good clinical condition after the 5-month follow-up. Conclusion The assessment of the respiratory distress in an infant with a mass centered by an axial skeleton on the chest x-ray and thoracic CT scan may suggest a diagnosis of intrathoracic FIF.